Speeches on the Indian difficulties in the North-West [electronic resource] - Cunningham, R. (Robert), 1836-1874.; Strathcona and Mount Royal, Donald Alexander Smith, Baron, 1820- 1914. ([Ottawa? : s.n.], 1873)
Electronic reproduction. Mode of access: Internet. 44